Comparison of Health-Related Physical Fitness Levels of Girls in Day and Boarding Senior High Schools in Cape Coast - Nordzro, Charity; Stephen Sorkpor, Richmond; Tsorhe, Bismark (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of the study was to find out any differences in the health-related physical fitness levels of day and boarding girls in the SHS in Cape Coast, Ghana. The study employed the descriptive survey design involving One hundred and sixty (160) respondents who are SHS girls from Aggrey Memorial Senior High School and Ghana National College were used for the study. The Prudential Fitnessgram (2002) battery of tests was used to test the five components of health-related physical fitness of each subject for the study. The scores were processed and analyzed using the independent samples t-test and the Healthy Fitness Zone (HFZ). From the HFZ values and the t-test statistics results, there is an indication that the boarding girls were at higher risk in respect to the health related physical fitness components tested. The day girls were fitter in all the five health-related physical fitness components tested. This may be due to the fact that the nature and intensity levels of physical activities differ between the two groups. The comparatively poor health-related physical fitness condition of the girls in the boarding house is not good at all and needs an urgent, practical and comprehensive approach to deal with it, such as designing physical education, sporting and recreational activities to be interesting and attractive for students to participate.